PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DI SMAN 15 PADANG - Medeti, Siti Florensia; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Student activity in learning activities is still low, it can be seen from students who cannot solve the problems posed by the teacher, find it difficult to explore their ideas or ideas in discussions, and students are still less active in participating and do not respond well to questions given by the teacher, this causes activity and low student learning interest affects the acquisition of student learning outcomes. This study aims to determine the effect of applying the project based learning model on geography learning outcomes. This study uses a quantitative approach with a quasi-experimental type. Researchers chose class X E2 by applying the project based learning model and X E4 using conventional methods. Data collection uses objective questions and documentation. Then, to find out whether or not there is an effect of applying the project based learning model, researchers use the t-test. The results obtained were the posttest average for the control class, which was 76.95 and the posttest average for the experimental class, which was 87.33, while the N gain for the control class was 35.92% and that for the experimental class was 62.86%. It can be concluded that the application of the project based learning model is quite effective in improving student learning outcomes.